Sickness absence of LU train drivers after track incidents. (14th July 2016) - Chavda, S.
Abstract: Background: Track incidents including near misses and those causing injury or death are a psychological hazard for train operators. No study has directly investigated how train operators are affected depending on track incident outcome and few studies have investigated the impact of near misses. Aims: To compare sickness absence (SA) of London Underground train operators following track incidents categorized by outcome, including near misses. Methods: This was an observational study using historical data of track incidents from April 2008 to October 2013. Track incidents were divided into four categories according to outcome (near miss on platform, near miss on track, significant injury and fatality). Additional information on age, gender and previous relevant history was collected. Results: A total of 685 track incidents were analysed. There was a significant difference in SA taken after near misses ('no injury') incidents compared with significant injury and fatality ('injury') incidents ( P < 0.001). There was also a significant difference in SA in train operators involved in a fatality incident compared with significant injury incidents ( P < 0.05). Conclusions: SA in train operators following a track incident increases in line with the severity of the incident in terms of outcome. Fatal track incidents caused the highest level of SA followed by significant injury incidents. Near misses also caused substantial levels of SA.